2006
DOI: 10.1016/j.jacc.2006.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Blood Viscosity and its Relationship to Iron Deficiency, Symptoms, and Exercise Capacity in Adults With Cyanotic Congenital Heart Disease

Abstract: Iron deficiency is common in cyanotic adults but does not alter viscosity. Hyperviscosity symptoms are associated with a higher Hct-adjusted viscosity independent of cell size or iron stores. Higher Hct is associated with better exercise capacity. Further work to understand the origin of hyperviscosity symptoms is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 43 publications
(43 reference statements)
3
95
1
4
Order By: Relevance
“…While Tilmann and Schroter (1980) and Vaya et al (2005) reported decreased erythrocyte deformability, some other authors stating normal values (Reinhart 1992). Moreover iron deficiency has no effect on blood viscosity even in patients with cyanotic heart diseases (Broberg et al 2006). An explanation for autonomic dysfunction in iron deficiency anemia can be low oxygen tension in tissues.…”
Section: Discussionmentioning
confidence: 97%
“…While Tilmann and Schroter (1980) and Vaya et al (2005) reported decreased erythrocyte deformability, some other authors stating normal values (Reinhart 1992). Moreover iron deficiency has no effect on blood viscosity even in patients with cyanotic heart diseases (Broberg et al 2006). An explanation for autonomic dysfunction in iron deficiency anemia can be low oxygen tension in tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Secondary erythrocytosis, commonly found in cyanotic CHD-PAH patients, represents a physiologic adaptation to improve oxygen delivery to the tissue [40]. As a consequence, routine phlebotomy is contraindicated as it impairs oxygen transport capacity, reduces exercise tolerance [41], induces iron deficient anemia [30] and augments the risk of stroke [42]. If unavoidable due to clear hyperviscosity symptoms, phlebotomy should only be performed in the absence of iron deficiency and by avoiding dehydration [40,43].…”
Section: Medical Therapy: General Aspectsmentioning
confidence: 99%
“…More than a third of CCHD patients are iron deficient [68][69][70]. Typical indices of iron deficiency including hypochromia and microcytosis are often absent; exclusion of iron deficiency, therefore, requires a complete iron metabolism workup, including serum ferritin and transferrin levels [68].…”
Section: Hematologic Consequences Of Cchdmentioning
confidence: 99%
“…Iron deficiency should be avoided in CCHD, with oral iron supplementation as needed to normalize ferritin levels remaining mindful of an overly robust rise in hematocrit [7]. Although physicians are often uncomfortable administering iron in patients with high hematocrit, supplementation has been shown to improve exercise capacity and quality of life in iron-deficient cyanotic patients without increasing hyperviscosity risk [69,72].…”
Section: Hematologic Consequences Of Cchdmentioning
confidence: 99%